2013
DOI: 10.1007/s11764-013-0317-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cancer diagnosis on employment: is there a difference between rural and urban populations?

Abstract: A cancer diagnosis may have a greater impact on employment among rural residents. Cancer programs should recognize this disparity and enhance return to work and disability counseling in patients from rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
3
13
1
Order By: Relevance
“…Participants identified a lack of local services, a need for travel to treatment and a disjuncture between treatment centres posing significant challenges for regional and remote cancer survivors when attempting to remain at/return to work, consistent with review findings indicating that travel to treatment causes practical and financial difficulty for rural survivors 27 . Some support was found for the hypothesis that this disparity may in part be due to higher proportions of regional/rural employment involving manual labour 19 . Further barriers included the lack of any available work and difficulty of employers in holding positions open for cancer survivors to return to.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Participants identified a lack of local services, a need for travel to treatment and a disjuncture between treatment centres posing significant challenges for regional and remote cancer survivors when attempting to remain at/return to work, consistent with review findings indicating that travel to treatment causes practical and financial difficulty for rural survivors 27 . Some support was found for the hypothesis that this disparity may in part be due to higher proportions of regional/rural employment involving manual labour 19 . Further barriers included the lack of any available work and difficulty of employers in holding positions open for cancer survivors to return to.…”
Section: Discussionsupporting
confidence: 59%
“…A European study found cancer survivors from lower socio‐economic groups were less likely to return to work and took longer to return or to regain employment than survivors from groups experiencing less socio‐economic disadvantage, despite routine offering of occupational rehabilitation to cancer survivors 20 . Authors of these studies argue the employment needs of rural cancer survivors and those living with socio‐economic disadvantage are distinct from the needs of other cancer survivors, due to the nature of occupations prevalent in these groups 19,20 . This is consistent with findings indicating that the employment gap for cancer survivors is larger for those employed in agriculture, forestry, fishery, transport, manufacturing and services, compared with those in sciences, humanities, administrative, managerial or clerical work 21 .…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Negative attitudes towards cancer survivors returning to work prevailed in rural areas, partly because rural residents are predisposed to believe that physical limitations among cancer survivors contribute to lower work productivity [ 13 ]. Sowden et al [ 14 ] showed that labor is more physically demanding in rural areas than in cities, and rural cancer survivors are more likely to retire early. In Finland, however, the capabilities of cancer survivors to work were not different from those of demographically matched healthy controls, and the ability of survivors diagnosed two years previously to engage in physical work had deteriorated by 26% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 Our study also showed that 39% of rural cancer survivors reduced their work hours; again, this proportion is higher than that of another study conducted in America (31%). 24 These occupational issues are profound as many rural cancer survivors are forced to rely on their limited savings to support themselves or rely on the support of their family members.…”
Section: F I G U R E 3 Changes In Work Hoursmentioning
confidence: 99%